2012
DOI: 10.1556/aphysiol.99.2012.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of radial blood flow during Braille character discrimination task

Abstract: Purpose: Human hands are excellent in performing sensory and motor function. We hypothesized that blood flow of the hand are dynamically regulated by sympathetic outflow during concentrated finger perception. To identify this hypothesis, we measured radial blood flow (RBF), radial vascular conductance (RVC), heart rate (HR), and arterial blood pressure (AP) during Braille reading performed under the blind condition in nine healthy subjects. The subjects were instructed to read a flat plate with raised letters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…We made flat plates with raised letters, as previously reported . The convexities (diameter: 3 mm, height: 1 mm) on the plates were arranged according to Braille code.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We made flat plates with raised letters, as previously reported . The convexities (diameter: 3 mm, height: 1 mm) on the plates were arranged according to Braille code.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have reported that radial blood flow, measured using an ultrasound Doppler system, is reduced via sympathetic nerve activity during a Braille character discrimination task . This decrease in radial blood flow during the Braille discrimination task may be followed by fluctuations in fingertip skin blood flow (SBF) and finger volume (FV), which in turn results in the deformation of the cutaneous tissues.…”
Section: Introductionmentioning
confidence: 99%